Potato yield with mineral fertilizer on Andosol soils in the State of Mexico - Morales Hernández José Luis; Hernández Martínez Juvencio; Rebollar Rebollar, Samuel (Revista Mexicana de Ciencias Agrícolas, 2018)
The experiment was conducted in an Andosol soil in the community of Peñuela, municipality of Zinacantepec, State of Mexico in 2009, with the objectives: a) evaluate the yield of potato tubers (Solanum tuberosum L.) cultivar Fianna, in response of nitrogen, phosphorus and potassium levels, with commercial fertilizer and b) estimate optimum economic levels for limited and unlimited capital. Nutrient levels subjected for evaluation were: 150, 200, 250, 300, 350 kg ha-1 of N, 00, 200, 250, 300, 350, 400, 450 kg ha-1 of P205, and 00, 70, 140, 210 kg ha-1 of K20. 18 treatments were designed, which were evaluated in an experimental design of randomized blocks, with four replications; responses to N, P205 and K20 were verified with the Turrent graphical method. The results indicate better yield capability in treatments four (34.3 t ha-1, 300-350-70 kg ha-1 N, P2O5, K2O) and seven (33.7 t ha-1: 150-250-70 kg ha-1 N, P2O5, K2O), both statistically different from the other treatments (α< 0.05), with a variation coefficient of 25.9%. The optimum economic of unlimited capital was located in treatment four (300-350-70 kg ha-1 of N, P2O5 and K2O), with a higher net income. The optimum economic for limited capital, was located in treatment seven. It is conclude that there is a yield response associated with optimal doses by the use of ammonium diphosphate, phosphonitrate and potassium chloride in the study region.